Effects of anchor borrowers′ programme on smallholder rice production risk and technical efficiency in Kebbi State, Nigeria - Kara, Hamidu Abubakar (2019)
Rice is Nigeria’s major staple crop and strategic for food safety. Besides the primary source of food its production provides millions of smallholder farmers with livelihoods. However, rice production in Nigeria has been extensive over the years. This has created a huge gap between supply and demand. The Nigerian government spends US$ 300 million annually on rice imports. Imports policy has discouraged domestic production, increased unemployment, and increased poverty. In the past, various funding actions were launched to encouraging domestic production, but the required goals were not accomplished because of the failure of smallholder farmers to access credit and profitable markets to dispose of their products. The Anchor Borrowers’ programme was launched in Kebbi state in 2015 to address the two fundamental issues facing smallholder farmers in boosting national output. The research aims to contribute to a clearer knowledge of the possible causes of rice production volatility in the Kebbi state Anchor Borrowers’ Programme. The output gap between the real output and achievable output presents an opportunity for output growth. Data from a total of two hundred and twenty-two loan beneficiaries and one hundred and fifty-five non-beneficiaries farms were gathered using a cluster sampling technique. The data were obtained from the survey conducted for the 2016 farming season. The research adopts a Trans-log stochastic frontier model with flexible risk properties to estimate efficiency levels while taking into account production risk. The variability of production from two sources, production risk and technical efficiency is therefore evaluated. Data envelopment analysis was also used to estimate the level of technical efficiency without accounting for production risk. Results show that the Trans-log production frontier is the best fit model for the mean output function of both the beneficiaries and non-beneficiaries. In their production methods, there is also the presence of technical inefficiency and production risk. The effects of technical inefficiency relate to exogenous variables. Input variable seeds, fertilizers, agrochemicals, and labour positively affect rice production for both the beneficiaries and non-beneficiaries. The research also demonstrates that the beneficiaries’ farms in the research region show increased scale yields while nonbeneficiaries decrease scale yields. Fertilizer and agrochemicals reduce the risk of output for the beneficiaries, likewise seeds and labour reduce the risk of output for non-beneficiaries. The variability of the input variable on the output risk could be ascribed to the variability in soil type, application rate, and technique of application among others. The mean technical efficiency estimated with the flexible risk element was 85.3 percent while without risk element was 65.5 percent for the beneficiaries. Similarly, the average technical efficiency estimated for non-beneficiaries with risk element was 77.6 percent while without risk element was 56.7 percent. There is a substantial distinction in the mean level of technical efficiency of the beneficiaries and non-beneficiaries as shown by independent t-test. The transplanting method used was the best farming practice that increases the efficiency of the beneficiaries and nonbeneficiaries. It was also realized that years of education, extension services and loan access significantly enhance the beneficiaries’ technical efficiency. The study proposes making rice inputs easily available, inexpensive and accessible to both the beneficiaries and non-beneficiaries. The beneficiaries should ensure the effective and proper use of fertilizer and agrochemicals to mitigate production risk while non-beneficiaries should appropriately use labour and seeds to mitigate risk. The beneficiaries and non-beneficiaries education should be encouraged, extension services and access to credit should be common to both.